(3GdObGFb GdeMceI aj TQM GdebOeI GdLRQjIs - (3RcQjG Hf eMeO Hf CMeO Hf RcQjG GdCfUGQj GdSfjcj GdeUQj GdTGaYqj, CHh jMji , J (B926 (3g` s; (3eMeO Hf eMeO Hf eMeO Hf Ydj Hf jhSa, CHh GdNjQ, TeS GdOjf, GdYeQj GdOeTbqj Ke GdTjQGRj GdTGaYqj, GdTgjQ HGHf GdLRQj,(B833 (3g`s ((3CMeO QaYJ s)
(3ChdgG (B:s
(3bGd TjNfG RcQjG GdCfUGQi GdMeO ddg GdPi EaJJM HGdMeO cJGHg hHYO aEf GdebOeI GdefXheI ai JLhjO GdbQBf ddTjN GdEeGe eMeO Hf eMeO Hf eMeO Hf GdLRQi MhJ ef UZQ GdMLe eGde jMhg ai gPG Gdaf cKjQ ef GdcJH GdcHGQ QCjJ Cf CVY Yds
(3BNQgG (B:s
(3Ci Ke HYO MeO Gddg GdUdGI hGdSdGe Ydi SjOfG hehdGfG eMeO hBdg hUMHg GdCWgGQ HNJGe dgG ceG Cf Pdc cGf EHJOGDgG ceG eQ JeJ HMSf Jhajbg SfI (B1285 (3g` s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdbQGAGJ hGdJLhjOs